Panathenaic Amphorae of Hellenistic and Roman Times - Streicher, Martin (Journal of Hellenistic Pottery and Material Culture, 2020)
Vases play a very significant role in understanding ancient cultures because they were associated with all areas of life in antiquity. This is especially true for the amphorae, which were awarded as prizes at the Panathenaic games in Athens. These Panathenaic amphorae are commonly found at different places across the Mediterranean region from around 560 BCE into the Roman period. They are characterized by a standardized iconographic scheme, which shows Athena on the front and the depiction of a sport’s competition on the reverse.